Analisis Kebijakan Amnesti Pajak dan Program Pengungkapan Sukarela Perspektif Maqashid Syariah - Aris Setiawan; Amrizal Amrizal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The main objective of this study is to evaluate the tax amnesty policy and voluntary disclosure program in the context of the principles of Maqashid Syariah, which include the protection of religion, life, mind, descendants, and property. The tax amnesty policy in Indonesia, introduced in 2016, managed to collect IDR 147 trillion from 1.1 million taxpayers, demonstrating the potential of this policy in improving tax compliance. However, challenges such as lack of public understanding and negative stigma towards taxes still need to be addressed. Voluntary disclosure programs have also shown mixed results, with the need to increase participation through better education. This study concludes that in order to achieve the objectives of maqashid syariah, this policy must be implemented with transparency, accountability, and social justice, so that it can provide significant benefits to society and the state. Recommendations to improve the effectiveness of this policy include better socialization, a strict monitoring system, and allocation of funds raised for social programs.